Online QR Pass for Event Management System - Rashshell, Matan (Universiti Malaysia Sarawak, (UNIMAS), 2020)
The output of the project is for the visitor to participate the event by booking the event and the event will generate QR code as the pass for the event entry.The system also will become a platform to promote event based on culture that related to any kind of local festival in Sarawak.The system will be developing using an open source programming language for web developer,in this case project will using an open source software meaning it is free of charge,and also the structured of the website will be associated with other programming language tool such as HTML 5,CSS,PHP,Javascript and MYSQL.This proposed system also require a database system in order to save the data regarding customer’s data or about the website itself.